(untitled) (Bulletin of Innovative Research, 2026)
This paper examines humanism as a key category in 20th-century Russian and Uzbek prose. It analyzes the artistic representation of humanistic ideas in the works of Mikhail Sholokhov and Utkir Khoshimov. Special attention is paid to the раскрытие внутреннего мира героев (reveal the inner world of characters), their moral choices, and their ability to preserve human dignity under conditions of historical upheaval. The study identifies similarities and differences in the interpretation of humanism within Russian and Uzbek literary traditions. It concludes that humanistic values are universal and play a significant role in the literary understanding of the human being in the 20th century.